Seeds germination in constant magnetic field - Ivanov I.V.; Sokolova L.A. (BIO Web of Conferences)
This work is devoted to the study of the influence of a constant magnetic field on the germination of spring wheat and white mustard seeds. In the experiment, the effect of the north and south poles of magnets on the dry mass of seedlings was studied. Two experiments were conducted: the first in three variants with fourfold repetition, the second in two variants with eightfold repetition. The induction of the artificially created magnetic field in the seeds location area did not exceed 14 mT. The dispersion analysis of the experimental results showed that, with a probability of 0.95, the magnetic field does not increase seedlings dry mass. During the experiment, increased moisture absorption in the presence of a magnetic field, as well as residual magnetization in seeds was not observed. For this reason, it was concluded that magnetic treatment of germinating seeds of these crops is impractical.